THE EFFECT RECOMBINANT GROWTH HORMONE (rGH) DOSES AND IMMERSION DURATION ON GROWTH AND SURVIVAL RATE OF TAMBAQUI LARVAE (Colossoma macropomum) - Sebayang, Nasha Putra; Nuraini, Nuraini; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT  This research was conducted on October9, 2020 - November 28, 2020, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Science Faculty of Riau University. The aim of this research was to determine the effect of Recombinant Growth Hormone (rGH) and the optimal dose and immersion duration on growth and survival rate of tambaqui larvae (Colossoma macropomum). The method used  was a Completely Randomized Design Factorial with 2 factors. The first factor was  the dose of rGH with 3 levels;  0 mg/L (D0), 1.5 mg/L (D1,5) and 2.5 mg/L (D2,5). The second factor was the immersion duration with three levels of 30 minutes (W30), 60 minutes (W60) and 90 minutes (W90) respectively. The larvae were cultured preserved in aquarium for 40 days with 2 fish/L density. The results showed that the use of different doses and  immersion duration of rGH effected  on absolute weight, absolute length, specific growth and survival rate of river catfish larvae. Treatment dose 1.5 mg /L and 60 minutes (D1,5W60) with the result of absolute weight growth of 2.88 grams, absolute length 4.87 cm, specific growth rate of 18.45 % and survival rate of 91.10 %. The water quality parameters during the study were optimal for river catfish larvae with temperature 26.7-27.9 oC, pH 5.9-6.9 and dissolved oxygen 6.3-7.3 mg/L. Keywords : Doses, Immersion Duration, Recombinant Growth Hormone, Colossoma macropomum.